Aspectos clínicos-epidemiológicos da criptococose no estado de Goiás - Bastos, Angelica Lima de (2017)
Cryptococcosis is a systemic mycosis associated with high lethality, with meningoencephalitis being the most serious and frequent form of infection. It is mainly caused by C. neoformans and C. gattii. C. neoformans is cosmopolitan and in general is associated with individuals with cellular immunosuppression related to HIV virus, while C. gattii is endemic in tropical and subtropical areas and is usually a primary pathogen in apparently immunocompetent hosts. The objective of this study was to characterize the clinical and epidemiological aspects of patients with cryptococcosis in the state of Goiás, Brazil, from 2011 to 2014, based on the analysis of laboratory data and medical records from reference units. We analyzed 130 cases with the following variables: sex, age, region, risk factors, signs and symptoms, clinical form of the disease, laboratory data, treatment, evolution and sequelae The following results were found: male predominance; age group of 31 to 40 years in HIV positive and over 50 years in HIV negative; majority of patients from Goiás and residents in capital (Goiânia); 89.2% were HIV positive and 10.8% were HIV negative. Also, the chronic use of immunosuppressive drugs was considered a risk factor in 64.3% of seronegatives; headache and fever were the main symptoms and meningoencephalitis was the predominant clinical form; C. neoformans was the most isolated species in culture of clinical specimens; the mean HIV-CD4 T-cell count was 58.66 cells / mm 3; the majority of patients where treated with amphotericin B during the induction phase of treatment; 60.8% of the patients died, of which 47.7% had cryptococcosis as the underlying or associated cause of death and among patients who survived; 43.1% of patients who survived had sequelae, with visual impairment being the most frequent. It is believed that the results obtained can be used as a database to document the clinical-epidemiological profile of patients with cryptococcosis in a tropical area and contribute with studies of global epidemiological epidemiology of the disease.